A Survey about the Prevalence of Dysmenorrhea in Female Students of Shahid Sadoughi University of Medical Sciences and Their Knowledge, and Practice toward it - Mohammad Hossein Baghianimoghadam; Azam Mohammad Loo; Hossein Falahzadeh; Mehdi Mirzaei Alavijeh (Shahid Sadoughi University of Medical Sciences, 2012)
Introduction: Dysmenorrhea is one of the most common and important health problems especially among young girls. It causes absence from classes and work. It has some negative effects on daily activities of patients. Because of cultural problems, patients ordinarily don't seek help from others in this situation. The aim of this survey was to study the prevalence of this disorder among university students and evaluate their knowledge and practice toward it. Materials & Methods: This was a descriptive study on 300 female students of Shahid Sadoughi University of Medical Sciences in Yazd. Subjects were selected by simple sampling. The data were collected by a researcher-made questionnaire. The data were analysed by SPSS (ver. 17) using Chi - Square and Kruskal-Wallis tests. Results: The age range of participants was 18 - 35 years (mean: 21±4.3 years). Prevalence of dysmenorrhea was 38.3% and the knowledge of 6.3% of students was good. There was a significant difference between participants regarding their knowledge and age. The first source of awareness of 39% of students was their mother. The practice of 17.7% of subjects was good. Discussion: the results of this study showed that the knowledge and practice of participants about dysmenorrhea was low, so there is necessary to plan training programs for university students.